Suitability Analysis Of Tobacco Cultivation Technique In Nagari Baruah Gunung - Nursamsi Nursamsi; Muhammad Syahfitra (Department of Crop Science, Faculty of Agriculture, Andalas University, 2023)
The problem with tobacco farmers in Nagari Baruah Gununang is a productivity. Tobacco productivity is below national productivity due to cultivation techniques that do not comply with standards. The research method uses suitability analysis to assess the level of suitability of cultivation techniques used by farmers in Nagari Baruah Gunuang. The level of suitability is analyzed using check sheet based on a likert scale by comparing farmers actual and standards cultivation. The research results show that suitability level of tobacco cultivation technique is 70%. This means that the cultivation techniques used by farmers are still classified as almost in accordance with standards. The stages of cultivation that do not meet standards are planting; fertilization; and weeding, watering and loosening. The problems that cause non-compliance with this standard are close spacing of plants, lack of use of manure and dolomite, inappropriate dosage and type of chemical fertilizer, and insufficient watering and irrigation.